Analysis of the mulazamah method in Arabic language teaching at Ma'had Salman Al-Farisi Karanganyar in the men's section - Ibnu Syahid, Luthfi Afif; Kholiq Hasan, Moh Abdul; Qosim, Muhammad Nanang (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
The Arabic language teaching curriculum plays a significant role in enhancing students’ proficiency and language skills. This study aims to examine the implementation of the Mulazamah method in Arabic language instruction at the Salman Al-Farisi Institute, an institution known for employing this traditional approach in teaching Sharia sciences, including Arabic. The researcher adopted a qualitative approach using analytical descriptive methods, with data collected through observation, interviews, and documentation. The findings reveal that the Mulazamah method—rooted in the traditional practice of students accompanying their teachers closely—is characterized by continuous companionship and progressive learning, conducted book by book and stage by stage. The curriculum is divided into two phases:Basic stage: Durus al-Lughah al-‘Arabiyyah by Dr. V. Abdur Rahim. Post-basic stage: Grammar books such as Al-Muqaddimah al-Ājurrūmiyyah, At-Tuhfah as-Saniyyah, Mutammimah al-Ājurrūmiyyah, and Ad-Durrah al-Bahiyyah, as well as morphology books like Al-Amtsilah at-Tasrīfiyyah and As-Sarf aṣ-Ṣaghīr. However, a major challenge in applying this method lies in the absence of a unified teaching strategy among instructors. Each teacher applies the method according to their own pedagogical judgment. This study may serve as a reference for educational policy improvement and further research into the effectiveness of traditional methods in Arabic language teaching.